2021
DOI: 10.3390/ijms22137119
|View full text |Cite
|
Sign up to set email alerts
|

Function of Circular RNAs in Fish and Their Potential Application as Biomarkers

Abstract: Circular RNAs (circRNAs) are an emerging class of regulatory RNAs with a covalently closed-loop structure formed during pre-mRNA splicing. Recent advances in high-throughput RNA sequencing and circRNA-specific computational tools have driven the development of novel approaches to their identification and functional characterization. CircRNAs are stable, developmentally regulated, and show tissue- and cell-type-specific expression across different taxonomic groups. They play a crucial role in regulating various… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
3
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 29 publications
(9 citation statements)
references
References 134 publications
(162 reference statements)
0
9
0
Order By: Relevance
“…In mammals, birds, and teleosts, it was reported that circRNA plays important roles in muscle growth regulation [ 41 , 68 , 69 , 70 ]. Moreover, there are also studies addressing the involvement of circRNAs in the ovary development and sex determination for birds and teleosts [ 43 , 44 , 71 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In mammals, birds, and teleosts, it was reported that circRNA plays important roles in muscle growth regulation [ 41 , 68 , 69 , 70 ]. Moreover, there are also studies addressing the involvement of circRNAs in the ovary development and sex determination for birds and teleosts [ 43 , 44 , 71 ].…”
Section: Discussionmentioning
confidence: 99%
“…CircRNA plays important roles in many biological and pathophysiological processes including immune, metabolism, skeletal muscle and fat tissue growth, follicle development, nerve system development, cell proliferation, and diseases [ 24 , 25 ], by decoying miRNAs, binding to protein, and translating into peptides [ 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 ]. In teleosts such as the large yellow croaker ( Larimichthys crocea ), the grass carp ( Ctenopharyngodon idellus ), and the Nile tilapia ( Oreochromis niloticus ), circRNAs have been identified to be involved in growth, immunity, and heat stress [ 36 , 37 , 38 , 39 , 40 , 41 ]. In C. semilaevis , circRNA has been reported to regulate sex determination and differentiation [ 42 , 43 , 44 ].…”
Section: Introductionmentioning
confidence: 99%
“…CircRNAs was first reported in viroids by Sanger et al, in 1976 ( Sanger et al, 1976 ). With the development of high-throughput sequencing and increased research interest in circRNAs, many bioinformatics tools have been improved to study circRNAs in the past few years ( Wang Y. et al, 2020 ; Rbbani et al, 2021 ; Yang et al, 2021 ). Especially, accumulating evidence demonstrates that circRNA expression is deregulated in AML compared with healthy control and reveals AML subgroup-specific signatures ( Li W. et al, 2017 ; Chen H. L. et al, 2018 ; Lv et al, 2018 ; Lux et al, 2021 ; Wang J. H. et al, 2021 ).…”
Section: Dysregulation Of Circrnas In Acute Myeloid Leukemia and Thei...mentioning
confidence: 99%
“…These processes require a coordinated expression of many genes and diverse molecular pathways. In recent years, an increasing number of studies have suggested the importance of epigenetic mechanisms, including non-coding RNAs, in fish muscle development [ 5 10 ]. In-depth knowledge about regulatory mechanisms involved in fish growth is essential to explore the observed phenotypic variation in aquaculture conditions.…”
Section: Introductionmentioning
confidence: 99%